The Multi-Architecture Performance of the Parallel Functional Language GPH - Trinder, P.W.; Loidl, H-W.; Barry, E.; Hammond, K.; Klusik, U.; Peyton Jones, Simon (Euro-Par 2000 "” Parallel Processing, 2000)
In principle, functional languages promise straightforward architecture-independent parallelism, because of their high level description of parallelism, dynamic management of parallelism and deterministic semantics. However, these language features come at the expense of a sophisticated compiler and/or runtime-system. The problem we address is whether such an elaborate system can deliver acceptable performance on a variety of parallel architectures. In particular we report performance measurements for the GUM runtime-system on eight parallel architectures, including massively parallel, distributed-memory, shared-memory and workstation networks.